CHOOSING OPTIONS OF SURGICAL TREATMENT FOR RECCURENT OROPHARYNGEAL CANCER - I. A. Zaderenko; A. M. Mudunov; S. B. Alieva; A. A. Ahundov (Опухоли головы и шеи)
Introduction. Cancer of the oral cavity comprises 6 % of all malignant tumors. Recurrences occur in 15–30  % of patients, 50 % have local recurrences, 25–30  % – regional. The choice of treatment depends on the location and stage of the recurrence.Objective. To choose optimal tactics for surgical treatment in patients with recurrent cancer of the oropharyngeal region.Materials and methods. The study included 314 patients with recurrent squamous cell carcinoma of the oropharyngeal region, who were treated at the N.N. Blokhin Russian Cancer Research Center and underwent surgical, combination, or conservative treatment.Results. Survival in respect to the time of relapse was 35,0 ± 2.0 % for early (in the course of a year) relapses and 63,0 ± 7.1 % for late (a year after treatment and longer) relapses. Five-year survival in respect to the type of treatment for early recurrences was 34.2 ± 6 % for surgical treatment, 7.7 ± 3.5 % for combination treatment, and 17.6 ± 4.6 % for conservative approach. For late relapses, it was 62.7 ± 5.9 %, 77.8 ± 10.6 %, and 59.2 ± 8.7 %, respectively. Surgical treatment was performed in the form of removal of recurrent tumors, resection and reconstruction using local flaps, extended combined surgeries, and laser or cryodestruction.Conclusion. The method of choice for treatment of recurrent tumors of oropharyngeal cancer is surgery in the form of an extended combined surgery with defect reconstruction using musculocutaneous flaps including the pectoralis major.